Citizens, context, and choice : how context shapes citizens' electoral choices - Dalton, Russell J.; Anderson, Christopher, 1966- (Oxford : Oxford University Press, 2011)
How do institutions and electoral systems matter for citizens' electoral choices? This study attempts to answer this question for contemporary democracies. The book assembles leading electoral researchers to examine citizen choice in over 30 democracies surveyed by the Comparative Study of Electoral Systems.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Political participation; Voting; Political sociology; Political psychology